The Effect of Resveratrol on the Composition and State of Lipids and the Activity of Phospholipase A2 During the Excitation and Regeneration of Somatic Nerves - Revin, Victor Vasilevich; Pinyaev, Sergey Ivanovich; Parchaykina, Marina Vladimirovna; Revina, Elvira Sergeevna; Maksimov, Georgiy Vladimirovich; Kuzmenko, Tatyana Pavlovna (Frontiers in Physiology, 2019)
It has been shown that in the somatic nerve’s lipids, both during excitation and transection, changes occur with the composition of individual phospholipids and in phospholipids fatty acids, which changes the phase state of the myelin and nerve fiber axolemma lipid bilayer. A main contribution in the development of degenerative processes in the nerve is depend on of the phospholipid’s fatty acid composition of change during the activation of both Ca2+ -dependent and Ca2+ -independent forms of phospholipase A2. At the same time, we detected quantitative changes in FI and DAG, which depend on the activation of the phosphoinositide cycle during excitation and during degeneration processes in the nerve conductors. The results indicate that myelin lipids and nerve fiber axolemmas are involved not only in the functioning of the peripheral nerves, but also the pathological processes underlying deep functional and structural disorders. The effect of resveratrol on regeneration processes in the damaged rat sciatic nerve has also been demonstrated.